ETHICAL CULTURE STRENGTHENING MODEL AT RESORT POLICE AS PART OF POLICE REFORM: A BOURDIEU’S HABITUS BASED APPROACH - Ahrie Sonta (Masyarakat Indonesia, 2018)
This research emerged from concerns over cultural reform within the Indonesian Police, which has yet to show expected results, compared to successfully materialized structural and instrumental changes within the frame of Police Reform in the past two decades. Ethical culture, in this research, is believed as ‘organizational capital’ that is needed by the Police to facilitate cultural change. Inquiry into police habitus at the Sidoarjo Resort Police as this research’s object, revealed some problems hindering institutional integrity, i.e.: reminders of paramilitary culture, police doxa as crime-fi ghter, insuff uctient and partial development of internal oversight system, absence of public participatory ethical infrastructure, and deonthologic or rule-based defi nition of ethical approach. In the time being, on personel integrity aspect, there found the following problems: limited comprehension of ethics as a philosophy and of public ethics as public offi cial’s code of conduct, absence of training on ethics in police education, absence of supporting symbolic capitals, and weaknesses within recruitment and socialization system for newly recruited offi cers. A model of ethical culture strengthening is thus developed to overcome the problems on institutional and personel integrity, particularly at the resort level police organization.